Local Community Perceptions of the Social Impact of Tourism Development in Kemiren Village, Glagah District, Banyuwangi Regency - Arif Luqman Hakim; Luchman Hakim; Edriana Pangestuti (Journal of Social Research, 2023)
The development of global tourism in recent decades has received exclusive attention from a number of government elites and continues to experience significant growth. Analyze tourism development in Kemiren Village based on tourism components (4A - attraction, accessibility, amenities, and ancillaries).  The type of research that will be used is qualitative descriptive research. Descriptive research is research that is carried out to determine the value of independent variables, either one or more variables (independent) without making comparisons, or linking with other variables.  The forest was cleared to be used as a village of Kemiren Village and led by a Village Head named Marjana alias Walik. Kemiren Village still shows a socio-cultural life system that carries the traditional values of Osing. Kemiren Village was designated as a tourist area for the Osing traditional village by the Governor of East Java Basofi Sudirman.  The conclusion is that tourism development in Kemiren Village has fulfilled all components of tourism, namely attraction, accessibility, amenities, and ancillaries (4A).  Attractions or attractions in Kemiren Village are developed from their main potential, namely from the socio-cultural aspect in the form of customs that are still strongly embraced among the community.